Actualización y documentación de procedimientos de control interno para el proceso misional de atención al asociado en la cooperativa futurista de ahorro y crédito de Neiva Cofaceneiva" (2022)
Savings and credit cooperatives, according to Art. 40 of Law 454 of 1998, are specialized cooperative organizations whose main function is to carry out financial activity exclusively with their associates. These cooperatives are entities of great importance in the Colombian economy, and it is relevant to recognize that they are not exempt from risks. These must be identified, measured and controlled in time, before they lead to possible losses, and affect the users who depend on the sector. Control is a key factor, not only to prevent risks, but also to improve processes, increase efficiency and effectiveness, all aimed at meeting the company's objectives. There are internal control models, based on international standards, such as COSO III, which allows internal control to be applied to any type of entity, according to its needs.